Grape Seed Proanthocyanidins Exert a Radioprotective Effect on the Testes and Intestines Through Antioxidant Effects and Inhibition of MAPK Signal Pathways - Shen, Hui; Han, Jun; Liu, Chunlei; Cao, Fei; Huang, Yijuan (Frontiers in Medicine, 2022)
The testes and intestines are highly sensitive to ionizing radiation. Low-dose radiation can cause infertility and enteritis. However, there is a lack of safe and efficient radioprotective agents. This study aims to investigate the radioprotective effects of grape seed proanthocyanidins (GSPs) on testicular and intestinal damage induced by ionizing radiation. In vitro, GSPs reduced the apoptosis and proliferation inhibition of mouse testicular stromal cells TM3 and human small intestinal crypt epithelial cells HIEC induced by ionizing radiation, and alleviated DNA double-strand breaks. In vivo, GSPs ameliorated the pathological damage of the testes and intestines induced by ionizing radiation, and protected the endocrine function of the testes and the barrier function of the intestines. In addition, we preliminarily proved that the radioprotective effect of GSPs is related to its antioxidant effect and inhibition of MAPK signaling pathways. Our results indicate that GSPs are expected to be a safe and effective radioprotective drug.